What is New in Gastrointestinal Stromal Tumor?. (September 2017) - Schaefer, Inga-Marie; Mariño-Enríquez, Adrián; Fletcher, Jonathan A.
Abstract : The classification "gastrointestinal stromal tumor" (GIST) became commonplace in the 1990s and since that time various advances have characterized the GIST lineage of origin, tyrosine kinase mutations, and mechanisms of response and resistance to targeted therapies. In addition to tyrosine kinase mutations and their constitutive activation of downstream signaling pathways, GISTs acquire a sequence of chromosomal aberrations. These include deletions of chromosomes 14q, 22q, 1p, and 15q, which harbor putative tumor suppressor genes required for stepwise progression from microscopic, preclinical forms of GIST (microGIST) to clinically relevant tumors with malignant potential. Recent advances extend our understanding of GIST biology beyond that of the oncogenic KIT/PDGFRA tyrosine kinases and beyond mechanisms of KIT/PDGFRA-inhibitor treatment response and resistance. These advances have characterized ETV1 as an essential interstitial cell of Cajal-GIST transcription factor in oncogenic KIT signaling pathways, and have characterized the biologically distinct subgroup of succinate dehydrogenase deficient GIST, which are particularly common in young adults. Also, recent discoveries of MAX and dystrophin genomic inactivation have expanded our understanding of GIST development and progression, showing that MAX inactivation is an early event fostering cell cycle activity, whereas dystrophin inactivation promotes invasion and metastasis.